The impact of COVID-19 pandemic on traumatic injuries in children: a longitudinal observational study - Arian Zaboli; Mara Molaro; Gianni Turcato; Serena Sibilio; Gloria Brigiari; Gaia Weissmann; Paola Cogo; Olaf Schmidt; Francesco Brigo (Emergency Care Journal)
The COVID-19 pandemic affected pediatric emergency department (ED) visits for traumatic injuries. This retrospective study analyzed data from Merano Hospital, Italy, spanning January 2018 to October 2022, focusing on standardized ED visits per 1000 orthopedic attendances. Findings indicated a significant decline in ED visits at the pandemic’s onset (March 2020), followed by a gradual increase until April 2022, when emergency measures ended. Fracture and orthopedic procedure rates remained stable, while dislocations saw a temporary increase, then declined significantly. Overall, the pandemic’s influence on pediatric trauma was minimal, with ED visits and injury patterns returning to pre-pandemic levels. These findings suggest that pandemic-related restrictions, including reduced outdoor activities and fewer traffic accidents, may have temporarily modified injury risk factors.